The Effects of Perfluoroalkyl and Alkyl Backbone Chains, Spacers, and Anchor Groups on the Performance of Organic Compounds as Corrosion Inhibitors for Aluminum Investigated Using an Integrative Experimental-Modeling Approach. Issue 7 (20th July 2021) - Milošev, I.; Kokalj, A.; Poberžnik, M.; Carrière, Ch.; Zimerl, D.; Iskra, J.; Nemes, A.; Szabó, D.; Zanna, S.; Seyeux, A.; Costa, D.; Rábai, J.; et al.
Abstract : The ability of surfactant-like compounds to inhibit the corrosion of aluminum in NaCl solution was systematically investigated. The basic idea of this study was to scrutinize the effect of type of backbone chain (alkyl and perfluoroalkyl), length of backbone chain (number of carbon atoms 7, 10, and 17), various anchor groups (carboxylic, thiol, and imidazole) and presence of alkylene and benzene spacers between perfluoroalkyl chain and anchor group. To tackle these effects, three model studies were designed for alkaline etched, superhydrophilic aluminum surface and then approached experimentally and by density functional theory modeling. This enabled us to decouple the adsorption affinity of selected anchor groups on the hydroxylated aluminum surface from the lateral intermolecular cohesive interactions between hydrophobic backbone chains. Fourteen compounds were used to study the changes in the surface composition, wettability and the electrochemical barrier properties. For the carboxylic anchor group, the length and type of chain are important for barrier properties and also for tuning the wettability of the surface. The addition of alkylene spacer to perfluoroalkyl chain significantly affects the properties of the modified surface. Thiol and imidazole anchor groups, however, are not efficient inhibitors regardless the type and length of backbone chains.